Role-Playing Cards Learning Models Based on Madura Ethnic Entrepreneurship Values to Increasing Students' Interest in Entrepreneurship - Utomo, Fajar; Disman; Wahab, Abdul Azis; Saripudin, Didin (Journal for Lesson and Learning Studies, 2023)
The research concerns the monotony of social studies learning and the low interest in entrepreneurship among students. This study aims to develop an RPC learning model based on the entrepreneurial values of the Madurese and then measure the results of testing the model and its effectiveness in increasing students' interest in entrepreneurship. This type of research is developed using the ADDIE model. The five stages include analysis, design, development, implementation, and evaluation. The research subjects in three trials were conducted in 10 schools. Data collection techniques were collected through observation, interviews, questionnaires, validation sheets, and documentation studies. At the same time, the practicality test carried out the data analysis technique, the N-Gain test. The results showed that the RPC learning model based on the entrepreneurial values of the Madurese was operationalized through five learning steps assisted by media cards (question cards and solution cards) and scenario texts. The results of limited trials concluded that 65% of the learning models were practical enough to be used in social studies learning. Furthermore, the results of extensive trials showed no significant obstacles, only suggestions for adding time during student discussion activities. The effectiveness of the learning model by calculating the pretest and posttest scores resulted in the conclusion that the level of effectiveness was categorized as quite effective in increasing students' interest in entrepreneurship.